The Effect Of Giving Health Education About Free Sex Using The method Brain M0pping On Changes In The Level Of Knowledge Of Class VIII Students - Surtini, Surtini (Universitas STRADA Indonesia, 2019)
Adolescents are the next generation of the nation, in Indonesia Adolescents have a considerable proportion. But juvenile delinquency is increasingly worrying, among others, free sex. This is because not yet the maximum sex education provided to adolescents, including information media. In health education the media has an important influence in delivering information. Mind Mapping was chosen as a medium in delivering sex education information. This study aims to determine the effect of giving sex education with media mind mapping to knowledge Research was conducted at SMPN 1 Bandung Tulungagung on February 4 - 12, 2018 to 50 respondents. Design Experimental with pre test - post test design. The population of all class VIII students with simple random sampling technique was in accordance with the inclusion criteria. The results showed that before being given sex education as many as 21 respondents had good grades. after being given sex education brain mopping 33 respondents had good grades. The Wilcoxon Test Sign Rank Test results show a value of p 0,000 (p <Î±) which means H0 is rejected. Brain mopping is more attractive to the brain because of the use of images, colors and keywords. It is recommended for further researchers to further examine the use of educational aids media.